Information literacy beyond library 2.0 - Godwin, Peter; Parker, Jo (Facet Pub., 2012)
This new book picks up where the best-selling "Information Literacy" meets "Library 2.0" left off. In the last three years the information environment has changed dramatically, becoming increasingly dominated by the social and the mobile. This new book asks where we are now, what is the same and what has changed, and, most crucially, how do we as information professionals respond to the new information literacy and become a central part of the revolution itself? Divided into three distinct sections, Part I explores the most recent trends in technology, consumption and literacy, while Part II is a resource bank of international case studies that demonstrate the key trends and their effect on information literacy and offer innovative ideas to put into practice. Part III assesses the impact of these changes on librarians and what skills and knowledge they must acquire to evolve alongside their users. This is essential reading offering practical strategies for all library and information practitioners and policy makers with responsibility for developing and delivering information literacy programmes to their users. It will also be of great interest to students of library and information studies particularly for modules relating to literacy, information behaviour and digital technologies